Kajian Sosial Budaya Terhadap Tradisi Mabuug-Buugan Di Desa Pakraman Kedonganan, Kecamatan Kuta Selatan, Kabupaten Badung - I Made Yogi Marantika; Ni Made Sri Uttami Dharmaningsih (Tampung Penyang, 2022)
The mabuug-buugan tradition is a bhuta yadnya ceremony which is held in the Mangrove forest in Pakraman Kedonganan Village, South Kuta District, Badung Regency. This tradition is full of educational values ​​and plays a role in the process of social and cultural interaction among the community. In this tradition, based on devotional service carried out with lascayra, it will give positive power. Positive power will give a direction that is aimed at divine values, so that it leads to the glory of God. By pitting positive forces, which in a positive sense is not winning a victory. However, fighting for a decent life and always walking on the path of truth (dharma) and maintaining the natural state (Tri Hita Karana) of the mangrove forest of Pakraman Kedonganan Village. The dharma victory will reflect the joy and excitement of the community to welcome the new year. As for the meaning contained in the mabuug-buugan tradition; religious meaning, social meaning of society, meaning of education, and meaning of natural harmony.